IDENTIFIKASI KARAKTERISTIK FISIK TERNAK KAMBING DI PULAU TIDORE - Eny Endrawati; Sri Lestari; Dwi Nur Happy Hariyono (Fakultas Pertanian Universitas Majalengka, 2022)
The aim of this study was to identify the potential of goat farming on Tidore island through the identification of physical characteristics, e.g. body coat color, coat color pattern, facial profile, beard profile, and back profile. The physical characteristics of 101 goats (11 males and 90 females; aged 1 to 2 years) were observed, tabulated, and analyzed using descriptive statistics as number of observations and percentage. The results showed that the majority of the studied goats had the following physical characteristics: a combination of brown and white and of black, white, and brown for body coat color in males (45.45%) and females (27.78%), respectively, striped coat color pattern (63.64% in males; 78.89% in females), straight facial profile (81.82% in males; 95.56% in females), bearded in males (63.64%) and beardless in females (95.56%), and straight back profile (81.82% in males; 91.11% in females). It can be concluded that the studied goat population had variations in the physical characteristics, suggesting their potential use as a basis for development of goat genetic resources on Tidore island.